Games as a service how free2play design can make better games - Clark, Oscar (Focal Press, 2014)
"The games industry is serious business and the role of a games designer has dramatically changed over just the last few years. Developers now have to rethink everything they know about the creative, technical and business challenges to adapt to the transition to games as a service. Games as a Service: How Free to Play Design Can Make Better Games has been written to help designers overcome many of the fears and misconceptions surrounding freemium and social games. It provides a framework to deliver better games rather than the 'evil' or 'manipulative' experiences some designers fear with the move away from wasteful Products to sustainable, trustworthy Services. Games as a Service features: - Step-by-Step guide to ethical social and freemium game design principles - Product Design techniques to help create commercial games without compromising fun - The Role of the Player Lifecycle from Discovery, Learning, Engaging, and Churning - End-of-chapter exercises providing a design framework for Game As A Service - Companion website (www.GamesAsAService.net) for designers to share ideas"--Back cover
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed February 20, 2014)
Keywords: Video games -- Design; Video games -- Economic aspects; Video games -- Marketing; Jeux sur Internet; Aspect économique; Jeux vidéo; Conception; GAMES; Video & Electronic